Sistem Keamanan Rumah Berbasis Iot (Internet Of Thing) Menggunakan Sensor PIR (Pyroelectric Infrared), Web Camera Dan Aplikasi Android - Saputra, Fanny Eka; Sari, Linna Oktaviana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Internet of Thing (IoT)- based home security system is a security system with an automatic system and connected to the internet network. Home security is an important thing to protect something valuable at home. The use of an IoT-based home security system can be applied such as wireless motion sensor and monitoring camera. Using a Pyroelectric infrared (PIR) sensor as a sensor to detect movement in a room, the PIR sensor can detect motion up to 6 meters and can be adjusted by rotating the tripot on the sensor. The monitoring camera uses an ESP32-cam which functions to monitor the conditions indoors and sends image data to the BLYNK application. Emergency calls are also embedded to increase the effectiveness of the system by making emergency calls to numbers registered to the system such as the numbers of neighbors or people entrusted with using the SIM800L and Arduino modules. An ESP32- cam camera is used as a remote monitoring camera. This system is controlled using the ESP8266 to turn on and off the module in the motion sensor processing section in the form of the ESP8266 and the PIR sensor and the camera monitoring section. The test results obtained that the sensor can detect motion and provide notification to the IFTTT application, sound an alarm and make an emergency call, along with the ESP32cam camera can send images to the BLYNK application. Keywords : IoT, PIR, ESP32-cam, ESP8266, IFTTT, BLYNK.